High‐Resolution, Ground‐Based Observations of the Lunar Sodium Exosphere During the Lunar Atmosphere and Dust Environment Explorer (LADEE) Mission. Issue 9 (23rd September 2018) - Kuruppuaratchi, D. C. P.; Mierkiewicz, E. J.; Oliversen, R. J.; Sarantos, M.; Derr, N. J.; Gallant, M. A.; Rosborough, S. A.; Freer, C. W.; Spalsbury, L. C.; Gardner, D. D.; Lupie, O. L.; Roesler, F. L.
Abstract: We present the first comprehensive set of lunar exospheric line width and line width derived effective temperatures as a function of lunar phase (66° waxing phase to 79° waning phase). Data were collected between November 2013 and May 2014 during six observing runs at the National Solar Observatory McMath‐Pierce Solar Telescope by applying high‐resolution Fabry‐Perot spectroscopy ( R 180, 000) to observe emission from exospheric sodium (5, 889.9509 Å, D2 line). The 3‐arc min field of view of the instrument, corresponding to 336 km at the mean lunar distance (384, 400 km), was positioned at several locations off the lunar limb; only equatorial observations taken out to 950 km are presented here. We find the sodium effective temperature distribution to be approximately a symmetric function of lunar phase with respect to full Moon. Within magnetotail passage we find temperatures in the range of 2500–9000 K. For phase angles greater than 40° we find that temperatures flatten out to 1700 K. Plain Language Summary: High spectral resolution observations of optical line emissions are used to investigate the morphology and dynamics of the lunar sodium exosphere. These observations were obtained from the National Solar Observatory McMath‐Pierce Solar Telescope, coincident with the Lunar Atmosphere and Dust Environment Explorer mission. The equatorial data presented here are the first comprehensive set of direct sodium emission line profile observations of the lunar exosphere. These observations will help constrain atmospheric and surface process modeling, and help quantify lunar exospheric source and escape mechanisms. Studying the morphology of the lunar exosphere with altitude and local time provides a useful laboratory for testing space weather effects at Earth and theoretical models of other bodies with similar exospheres (e.g., Mercury). Key Points: Comprehensive sets of direct lunar exospheric line width observations are presented as a function of lunar phase Exospheric temperatures are highest near full Moon and decrease toward large phase angles Photon stimulated desorption dominates source mechanisms at subsolar points, with contributions by other processes near terminators